May '68 : Shaping Political Generations - Pagis, Julie, 1980- (Book collections on Project MUSE., 2018)
Much as in other locations around the world, civil uprising, particularly rooted in the activism of young people and students, plagued France during May of 1968. Massive strikes and occupations succeeded in paralyzing France?s economy and bringing the country to the verge of a leftist revolution. This book studies the life trajectories of many ordinary protestors during the period, using statistics and personal narratives to analyze how this activism arose, its impact on people?s personal and professional lives, and its transmission through familial generations.